2009
DOI: 10.1016/j.jtbi.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of reciprocity in sizable human groups

Abstract: The scale and complexity of human cooperation is an important and unresolved evolutionary puzzle. This article uses the finitely repeated n person Prisoners' Dilemma game to illustrate how sapience can greatly enhance group-selection effects and lead to the evolutionary stability of cooperation in large groups. This affords a simple and direct explanation of the human "exception".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, reciprocity is a discernable pattern of behavior when individual actions are observable, particularly in settings that experiments are designed to mimic. Furthermore, reciprocal strategies evolved to support cooperative behavior, [9,20,21,30] so observations of reciprocal behavior can signal a simultaneous observation of cooperation to some degree. Measuring cooperation in the real world therefore entails detecting processes that sustain it and comparing them to patterns found in a laboratory or theoretical setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, reciprocity is a discernable pattern of behavior when individual actions are observable, particularly in settings that experiments are designed to mimic. Furthermore, reciprocal strategies evolved to support cooperative behavior, [9,20,21,30] so observations of reciprocal behavior can signal a simultaneous observation of cooperation to some degree. Measuring cooperation in the real world therefore entails detecting processes that sustain it and comparing them to patterns found in a laboratory or theoretical setting.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that there is a possibility of graded strategies other than TFT in those situations where individuals interact with many other individuals simultaneously [9]. In such situations, reciprocal cooperation crucially depends on group size [10]. In addition, continuous strategies may perform better when group size increases [11].…”
Section: Introductionmentioning
confidence: 99%